PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM (Media Riset Akuntansi, 2022)
This study aims to examine the effect of profitability, leverage and firm size on stock return. The difference in results from previous studies motivates the authors to reexamine the effect of profitability, leverage and firm size on stock return. The theory that underlies this research is signaling theory and fundamental analysis. The population in this study are companies listed on index LQ45 the Indonesia Stock Exchange (IDX) for the period 2016-2020. Through purposive sampling technique with certain criteria obtained 210 sample companies for five years of observation. Data analysis in this study using multiple regression. The result of the study concluded that profitability and leverage had a positive effect on the stock return. In addition, leverage has no effect on the stock return. The research is expected to provide theoretical contribution for financial accounting research and practical contribution for the companies and investors.